The Political Economy of Multilateral Aid Funds - Jenny Simon; Justin Mattias Valasek (Center for Economic Studies and ifo Institute (CESifo), 2016)
In 2014 over 60 billion was mobilized to help developing nations mitigate climate change, an amount equivalent to the GDP of Kenya. Interestingly, breaking from the traditional model of bilateral aid, donor countries distributed nearly fifty percent of their aid through multilateral aid funds (OECD, 2015). In this paper, we show that by delegating aid spending to an international fund, donor countries mitigate a “hold-up” problem that occurs when donor countries are tempted to allocate aid based on, say, a regional preference. That is, under bilateral aid, donor-country bias decreases the incentive of recipient countries to invest in measures such as good governance that increase the effectiveness of aid. By delegating allocation decisions to a fund, however, donor countries commit to allocating aid via centralized bargaining, which provides recipient countries with an increased incentive to invest. Additionally, we show that allocating funding by majority rule further increases recipient-country investment, since higher investment increases the probability that a recipient's project will be selected by the endogenous majority coalition, and detail conditions under which majority is the optimal voting rule.
Keywords: F35; O19; H87; 330; aid policy; climate change; international organizations